" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
3x²y - x² + 4 xy² + x²y + 2x² =
= (3+1) x²y + (-1+2) x² + (4) xy²
= (4) x²y + (1) x² + (4) xy²
variabel = x²y, x² dan xy²
koefisien = (4), (1), ( 4)
kontanta = 0 ( tidk ada)
suku = 3
2)
(x+4)(y-3) = (1) xy + (4) y +(-3) x + (-12)
variable = xy, y , x
koef = (1), (4), (-3),
kontanta = (-12)
suku = 3
3)
3 pq² - 2q² - p + p²q + 3q² - 2p
= (3) pq² + (-2+3) q² + (-1-2) p + (1) p²q
= (3) pq² + (1) q² + (-3) p + (1) p²q
variabel = pq² , q² , p, p²q,
koef = (3), (1), (-3), (1)
konstanta = 0 tidak ada
suku = 4